Tinea incognito due to misuse of steroids and whitening body lotion: a case report - Rifa Imaroh; Maria Angela Lumaksono; Rien Hardiati; Izzah Imani; Dhelya Widasmara (Explorer Front, 2025)
Background: Tinea incognito (TI) is a dermatophytic infection with atypical clinical manifestations resulting from inappropriate use of topical corticosteroids. The misuse of over-the-counter steroids and unregulated cosmetic products, such as whitening body lotions, can alter the classical presentation of dermatophytosis, leading to delayed diagnosis and treatment failure. This case report aims to highlight the clinical features of tinea incognito associated with topical steroid misuse and whitening body lotion application, emphasizing the importance of early recognition and appropriate management to prevent misdiagnosis and treatment delay. Case: A 29-year-old woman presented with persistent pruritic erythematous patches on her back that had progressively enlarged over two months. The lesions initially appeared as small erythematous patches and were treated with topical corticosteroids prescribed by non-physician health practitioners. The patient continued self-medication with freely purchased topical steroids without improvement. She subsequently applied a whitening body lotion in an attempt to resolve the lesions; however, the patches worsened and expanded. Physical examination of the thoracolumbosacral region revealed ill-defined erythematous plaques with multiple peripheral erythematous papules and fine scaling. Laboratory examinations were not performed. The diagnosis of tinea incognito was established based on clinical history and physical findings. Treatment consisted of oral ketoconazole 200 mg daily, topical ketoconazole 2% cream, ketoconazole 2% shampoo twice weekly, nonsteroidal moisturizer, and antihistamines for two weeks. The patient was advised to discontinue topical steroids and whitening body lotion and received education on clean and healthy living behaviors. Significant clinical improvement was observed during follow-up. Conclusion: Discontinuation of topical steroids and inappropriate cosmetic products, combined with appropriate antifungal therapy, resulted in favorable clinical outcomes. Improved regulation of steroid and cosmetic product distribution, along with increased awareness among healthcare providers, is essential to prevent misdiagnosis and the rising incidence of tinea incognito.